Financial Well-Being: Indications on Buy Now Pay Later Users in Indonesia - Intantri, Cella Nur; Santi, Fitri (Universitas Mercu Buana, 2025)
Buy Now Pay Later (BNPL) is a payment method that allows consumers to purchase goods and pay for them later within a specified period. This study aims to explore the influence of financial knowledge, financial behavior, and self-control on the financial well-being of BNPL users in Indonesia, where the service is becoming increasingly popular, particularly among the younger generation. The research sample focuses on Millennials and Gen Z in Indonesia who have used BNPL services in the past six months. The analytical tool used is Partial Least Squares-Structural Equation Modeling (PLS-SEM) based on SmartPLS. The results indicate that while financial knowledge is only meaningful when mediated by financial behaviour, financial behaviour and self-control have a beneficial impact on financial well-being. These findings highlight the importance of financial education and the role of BNPL providers in offering features such as payment reminders and credit limits to support users' financial well-being.